Excellent energy absorption capacity of nanostructured Cu–Zn thin-walled tube - Afrasiab, M.; Faraji, G.; Tavakkoli, V.; Mashhadi, M.M.; Bushroa, Abdul Razak (Elsevier, 2014)
The present study shows that nanostructured (NS) thin-walled tubes possess an excellent energy absorption capacity, which was increased about four times compared to their course grained counterparts. Different deformation modes of axisymmetric concertina folding, three lobes diamond, and two lobe diamond forms were observed in annealed, single pass and two pass parallel tubular channel angular pressing (PTCAP) processed tubes, respectively.